1996
DOI: 10.1148/radiology.200.1.8657908
|View full text |Cite
|
Sign up to set email alerts
|

Severe ascites: efficacy of the transjugular intrahepatic portosystemic shunt in treatment.

Abstract: TIPS placement appears to be effective as a primary treatment of patients with cirrhosis and severe ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
2
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 0 publications
0
15
2
3
Order By: Relevance
“…[10][11][12][13][14] A number of studies have also shown that the reduction in portal pressure induced by TIPS is associated with beneficial effects on renal function and neurohumoral factors in patients with cirrhosis and ascites, including an increase in sodium and water excretion and a reduction in the activity of vasoconstrictor and antinatriuretic systems. [15][16][17][18][19][20][21][22] By contrast, the effects of TIPS in patients with HRS are not well characterized. Several case reports and preliminary data suggest that TIPS may improve renal function in cirrhotic patients with HRS.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] A number of studies have also shown that the reduction in portal pressure induced by TIPS is associated with beneficial effects on renal function and neurohumoral factors in patients with cirrhosis and ascites, including an increase in sodium and water excretion and a reduction in the activity of vasoconstrictor and antinatriuretic systems. [15][16][17][18][19][20][21][22] By contrast, the effects of TIPS in patients with HRS are not well characterized. Several case reports and preliminary data suggest that TIPS may improve renal function in cirrhotic patients with HRS.…”
mentioning
confidence: 99%
“…13 Doppler study of the TIPS and veins was obthe chest in patients with hepatic hydrothorax. TIPS patency.…”
mentioning
confidence: 99%
“…In unserer Studie lag die Überlebenswahrscheinlichkeit sechs Monate nach TIPS-Anlage bei 69 %. Dies ist mit den Resultaten anderer Arbeiten vergleichbar, die Überlebenswahrscheinlichkeiten zwischen 52 % und 75 % nach einem halben Jahr aufwiesen (Crenshaw et al 1996, Nazarian et al 1997, Ochs et al 1995, Quiroga et al 1995. Anhand der Ergebnisse lässt sich die schlechte …”
Section: üBerlebenszeit Nach Tips-implantationunclassified
“…Andere Studien hatten Stenoseraten der implantierten Stents zwischen 22 % und 60 % (Crenshaw et al 1996, Nazarian et al 1997, Ochs et al 1995. In der vorliegenden Arbeit besteht eine vergleichbar positiv niedrige Stenoserate aufgrund einer guten TIPS-Funktion.…”
Section: Revisionenunclassified
See 1 more Smart Citation